Analysis of the Digital Skills in the Eu Labor Market. a Case Study of the Banking Sector. (European Journal of Marketing and Economics, 2025)
The digitisation of the economy has been a global trend in the last decade and more significantly during the last five years. The European Union recognises that digitalisation changes the structure of the labour market, affecting employment and income distribution. Over the last ten years, digital technologies have entered more and more sectors of the European economy. Over 40% of EU workers have been involved in changing and/or replacing the technologies they use at work. Structural changes in the labour market in Europe are closely correlated with the very high demand for advanced digital skills in the coming years.This paper analyses the political, economic, socio-cultural and technological factors affecting the development of digital skills in the European Union (PEST analysis), with a focus on the banking sector.
Keywords: digital skills; digital competences; ICT; labour market; digitalisation